Detection of Foot and Mouth Disease Virus in Salted Raw Cowhide from Malaysia in Tanjung Priok Port, Indonesia - Sekarsana, Disty Ayu; Basri, Chaerul; Lukman, Denny Widaya (Universitas Airlangga, 2024)
Animal products such as raw salted cowhide are thought to have the potential to transmit the foot and mouth disease (FMD) virus from the infected zone. Indonesia imports raw salted cowhide from Malaysia, so it has the potential to transmit FMD to Indonesia which enters through Tanjung Priok Port. This study aimed to investigate the presence of the FMD virus in raw salted cowhide from Malaysia. The number of samples was collected from each container of raw salted cowhide imported through Tanjung Priok Port during August–December 2022. A total of 21 samples were obtained from 21 bulk containers containing raw salted cowhide. Real time q Polymerase Chain Reaction (RT-qPCR) was used to investigate foot and mouth disease virus in samples. The RT-qPCR screening test on 21 samples reported that salted raw cowhide was free from the FMD virus. Continuous monitoring and surveillance protocols for salted rawhide imported from non-free countries need to be carried out at other points of entry.